2010
DOI: 10.2174/157016210790442696
|View full text |Cite
|
Sign up to set email alerts
|

Does HIV VCT Reduce Risk Behaviors? An Observational Study in Guatemala City

Abstract: Voluntary counseling and testing resulted in changes in some self-reported risk behaviors, but only among HIV positive subjects. On nearly all measures men report riskier behavior than women. Alcohol is the most commonly used drug in this population and is often used with sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Condom use consistency in the previous three months among PLHIV in Guatemala in another study [8] is lower than condom use consistency reported by the sample in our study in the previous six months. Nevertheless, the sample in the other study was different from ours: homosexual and bisexual PLHIV were not excluded, they were more recently diagnosed with HIV, they had received less condom counselling, and they were not undergoing antiretroviral therapy.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Condom use consistency in the previous three months among PLHIV in Guatemala in another study [8] is lower than condom use consistency reported by the sample in our study in the previous six months. Nevertheless, the sample in the other study was different from ours: homosexual and bisexual PLHIV were not excluded, they were more recently diagnosed with HIV, they had received less condom counselling, and they were not undergoing antiretroviral therapy.…”
Section: Discussioncontrasting
confidence: 96%
“…Initially, before being counselled and diagnosed with HIV; 12.19% (5) of the sample (41 persons) stated that they had never had unprotected sexual relations in the prior three months. On the follow up visit, three months after counselling and diagnosis, 73.17% reported never having unprotected sexual relations in the prior three months [8]. This difference was statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies, one among individuals and one among couples, were multi-site, with locations in Trinidad, Kenya, and Tanzania (19, 20). The remaining five studies took place in the following locations: two in China (29, 30), two in Thailand (31, 32), and one in Guatemala (33). Most studies (N=12) took place in an urban location, while three took place in rural settings (15, 18, 30), one took place in a peri-urban setting (31), and one took place in a mixed setting involving both urban and rural locations (28).…”
Section: Resultsmentioning
confidence: 99%
“…Combined, the 17 studies included a total baseline population of 40,309 participants. Study designs included one individual-randomized trial (19, 20), two group-randomized trials (1921), three prospective cohort studies (15, 18, 27), eight before/after studies with no comparison group (2325, 2831, 33), one time-series study (22), and two cross-sectional studies (26, 32). …”
Section: Resultsmentioning
confidence: 99%
“…Recent HIV-prevention programmes have focused on counselling HIV-positive individuals to reduce their own risk behaviour as a way to limit transmission of the virus (Gerbert, Danley, Herzig, Clanon, Ciccarone, Gilbert & Allerton, 2006; Gilbert, Ciccarone, Gansky, Bangsberg, Clanon, McPhee et al ., 2008; Samayoa, Anderson, O’Sullivan, Patricia, Pacheco, Matos et al ., 2010). Other HIV-prevention programmes have focused on helping HIV-negative persons avoid infection (Abdool Karim, Sibeko & Baxter, 2010).…”
Section: Introductionmentioning
confidence: 99%